2014
DOI: 10.1117/1.jbo.19.3.035007
|View full text |Cite
|
Sign up to set email alerts
|

Porcine skin damage thresholds for 0.6 to 9.5 cm beam diameters from 1070-nm continuous-wave infrared laser radiation

Abstract: There is an increasing use of high-power fiber lasers in manufacturing and telecommunications industries operating in the infrared spectrum between 1000 and 2000 nm, which are advertised to provide as much as 10 kW continuous output power at 1070 nm. Safety standards have traditionally been based on experimental and modeling investigations with scant data available for these wavelengths. A series of studies using 1070-nm infrared lasers to determine the minimum visible lesion damage thresholds in skin using th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 22 publications
1
19
0
Order By: Relevance
“…The relationship also fits a power function, specifically: where m T is the aforementioned thermal slope term (°C∕J∕cm 2 ) and t is the total sequence duration (s). This finding is compatible with the observations made by Vincelette et al 8 and Oliver et al, 12 who noted lower peak temperature changes at longer exposure duration ED 50 s compared to shorter exposure duration ED 50 s.…”
Section: Number Of Pulsessupporting
confidence: 93%
See 4 more Smart Citations
“…The relationship also fits a power function, specifically: where m T is the aforementioned thermal slope term (°C∕J∕cm 2 ) and t is the total sequence duration (s). This finding is compatible with the observations made by Vincelette et al 8 and Oliver et al, 12 who noted lower peak temperature changes at longer exposure duration ED 50 s compared to shorter exposure duration ED 50 s.…”
Section: Number Of Pulsessupporting
confidence: 93%
“…Oliver et al 12 observed that for CW exposures to 1319-nm laser radiation for 0.25, 1, 2.5, and 10 s at two different beam diameters, only the 0.25-s cases featured a 1-h ED 50 that was greater than its 24-h counterpart. However, Vincelette et al 8 found that the 1-h ED 50 was greater than the 24-h ED 50 in 13 of 16 cases for 1070-nm laser radiation, across a wide range Table 3 Probit results for lesions 1 and 24 h after exposure to 1070-nm laser pulses with a beam diameter of 0.973 cm (1∕e 2 ). The laser total on-time for each set of parameters is 10 s. of exposure durations and beam diameters.…”
Section: Probit Analysismentioning
confidence: 99%
See 3 more Smart Citations